2009
DOI: 10.1097/ta.0b013e31819dc688
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients With Anterior Abdominal Stab Wounds: A Western Trauma Association Multicenter Trial

Abstract: Shock, evisceration, and peritonitis warrant immediate LAP after AASW. Patients without these findings can be safely observed for signs or symptoms of bleeding or hollow viscus injury. To limit the number of hospital admissions, we propose a uniform strategy using LWE to ascertain the depth of penetration; the patient may be safely discharged in the absence of peritoneal violation. Peritoneal penetration, absent evidence of ongoing hemorrhage or hollow viscus injury, should not be considered an indication for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 38 publications
8
101
0
2
Order By: Relevance
“…In series where patients with penetrating injuries undergo routine explorative laparotomy, it has been shown that approxi- mately 30-50% of these patients do not actually require treatment (negative laparotomy) (21)(22)(23). In our study, the negative laparotomy rate was 28% and we believe this rate will decrease with more rigorous clinical and laboratory evaluation and perhaps with more effective use of diagnostic laparoscopy.…”
Section: Discussionmentioning
confidence: 60%
“…In series where patients with penetrating injuries undergo routine explorative laparotomy, it has been shown that approxi- mately 30-50% of these patients do not actually require treatment (negative laparotomy) (21)(22)(23). In our study, the negative laparotomy rate was 28% and we believe this rate will decrease with more rigorous clinical and laboratory evaluation and perhaps with more effective use of diagnostic laparoscopy.…”
Section: Discussionmentioning
confidence: 60%
“…Laparotomide gözden kaçan yaralanmaların başlıca sebepleri ise yetersiz cerrahi eksplorasyon, zayıf cerrahi teknik ya da cerrahın deneyimsizliğidir (2,4). Yüksek kinetik enerjili silahlarla meydana gelen abdominal yaralanmalarda uygun görüş sağlamak için ksifoidden pubise kadar uzanan orta hat insizyonu yapılmalıdır.…”
Section: Discussionunclassified
“…4,5 One study found that 50% of patients who sustained blunt trauma with equivocal findings and underwent a laparoscopy avoided the necessity for a laparotomy. 27 In other centres, the use of laparoscopic procedures resulted in a 70-80% reduction in the number of nontherapeutic laparotomies. 11,28 This reduction may be due to the tremendous improvement in laparoscopic techniques and tools over the past few decades.…”
Section: Benefits Of Laparoscopymentioning
confidence: 99%